4-Benzyl-3-(2-Hydroxyphenyl)-1H-1,2,4-Triazole-5(4H)-thione - Dege, N.; Cetin, A.; Cansiz, A.; Şekerci, M.; Kazaz, C.; Dinçer, M.; Büyuk̈güngör, O. (Blackwell Munksgaard, 2004)
In the title molecule, C15H13N3OS, the triazole ring plane forms dihedral angles of 18.99 (7) and 89.35 (7)° with the hydroxyphenyl and benzyl substituent ring planes, respectively. In the crystal structure, the molecules exist as centrosymmetric N - H⋯S hydrogen-bonded dimers, with an N⋯S distance of 3.287 (2) Å. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.